They Just Don't Get Me: A Qualitative Analysis of Transgender Women's Health Care Experiences and Clinician Interactions - Hines, Dana D. (J Assoc Nurses AIDS Care, 2019)
Transgender individuals face many barriers when accessing health care, including having to teach clinicians how to care for them to receive appropriate care. We conducted a secondary analysis of qualitative data collected via semistructured interviews with 18 transgender women ranging in age from 21 to 60 years and living with HIV. Data were analyzed using conventional content analysis. Participants encountered two clinician types: Those who get me and Those who don't get me. Clinicians who get me provided gender-affirming care, fostered patient engagement, performed appropriate health screenings, and were willing to learn about transgender health. Clinicians who don't get me were aloof, uninterested, and unwilling to provide care. Clinicians who don't get me and system-level factors such as fragmented care, lack of insurance, and a low volume of transgender-competent clinicians contributed to transgender women's unmet health and education needs. Recommendations for improving transgender health care are provided.